Regaining mandibular position after hemimandibulectomy using ancillary maxillofacial prosthesis - Ahila S Chidembaranathan; Culathur Thulasingam (Wolters Kluwer Medknow Publications, 2023)
Fracture of any part of the mandible leads to deviation of the remaining portion of the mandible toward the fracture site and alteration of the biting surface of the teeth. Surgical resection of the mandible more commonly affects physiological, psychological, and esthetic effects of an individual. In such kind of patient, a buccal-based guidance appliance had an effective role in reducing or correcting the deviation of the mandible. This case report describes the prosthetic rehabilitation of resected mandible on the right side, and the deviation was corrected using guide flange ancillary maxillofacial prosthesis with a novel design. The guide flange prosthesis along with regular exercise minimizes the deviation of the mandible which further improves the masticatory efficiency and quality of life.